Atividade antimicrobiana de cimentos endodônticos - Mascarenhas, Ana Carolina Oliveira; Duque, Cristiane [UNESP] (My University, 2013)
The antimicrobial activity is a fundamental property of root-canal sealers due to persistence of residual microorganisms in the root canal system, even after the chemo-mechanical preparation and using of intracanal dressing. The aim of this study is to review the literature about the antimicrobial properties of some of the main root-canal sealers. Although there is controversy regarding this property, probably due to differences in the methodologies used in the studies, it was concluded that the sealers with the best antimicrobial activity were (in ascending order): Endofill, Ketac Endo, Sealapex, AH Plus, Endo CPM Sealer, Sealer 26 and Epiphany. Activ GP still needs scientific research to evaluate this property.

A atividade antimicrobiana é uma propriedade fundamental dos cimentos endodônticos devido à permanência de microrganismos residuais no canal radicular, mesmo após o preparo químico-mecânico e o emprego do curativo de demora. O objetivo deste trabalho é realizar uma revisão de literatura a respeito das propriedades antimicrobianas de alguns dos principais cimentos endodônticos. Embora haja controvérsias em relação a essa propriedade, possivelmente devido a diferenças nas metodologias empregadas nos estudos, pode-se concluir que os cimentos com melhor atividade antimicrobiana foram (em ordem crescente): Endofill, Ketac Endo, Sealapex, AH Plus, Endo CPM Sealer, Sealer 26 e Epiphany. Activ GP ainda necessita de pesquisas científicas que avaliem essa propriedade.
Antimicrobial activity of root-canal sealers
Keywords: Products with antimicrobial action; Dental cements; Root canal obturation; Produtos com ação antimicrobiana; Cimentos dentários; Obturação do canal radicular